Modelling short-term interest rate spreads in the euro money market - Nuno Cassola; Claudio Morana (European Central Bank (ECB), 2008)
In the framework of a new money market econometric model, we assess the degree of precision achieved by the European Central Bank ECB) in meeting its operational target for the short-term interest rate and the impact of the U.S. sub-prime credit crisis on the euro money market during the second half of 2007. This is done in two steps. Firstly, the long-term behaviour of interest rates with one-week maturity is investigated by testing for co-breaking and for homogeneity of spreads against the minimum bid rate (MBR, the key policy rate). These tests capture the idea that successful steering of very short-term interest rates is inconsistent with the existence of more than one common trend driving the one-week interest rates and/or with nonstationarity of the spreads among interest rates of the same maturity (or measured against the MBR). Secondly, the impact of several shocks to the spreads (e.g. interest rate expectations, volumes of open market operations, interest rate volatility, policy interventions, and credit risk) is assessed by jointly modelling their behaviour. We show that, after August 2007, euro area commercial banks started paying a premium to participate in the ECB liquidity auctions. This puzzling phenomenon can be understood by the interplay between, on the one hand, adverse selection in the interbank market and, on the other hand, the broad range of collateral accepted by the ECB. We also show that after August 2007, the ECB steered the “risk-free” rate close to the policy rate, but has not fully off-set the impact of the credit events on other money market rates.
Keywords: C32; E43; E50; E58; G15; 330; co-breaking; Credit risk; euro area; fractional co-integration; fractionally integrated factor vector autoregressive model; liquidity risk; long memory; money market interest rates; Structural change; sub-prime credit crisis; Geldmarkt; Makroökonometrie; Zinsstruktur; Euromarkt; Subprime-Krise; Finanzkrise; EU-Staaten; USA